Values, Environmental Beliefs, and Connection With Nature as Predictive Factors of the Pro-environmental Vote in Spain - Aguilar-Luzón, M. Carmen; Carmona, Beatriz; Calvo-Salguero, Antonia; Castillo Valdivieso, Pedro A. (Frontiers in Psychology, 2020)
This research analyzes the predictive capacity of psychosocial variables that can influence the decision to vote for political parties that include pro-environmental measures in their program. To this end, a study was carried out with a sample of 414 people of legal age who could exercise their right to vote (mean age = 26.92, SD = 10.53). The participants were divided into two groups: 1) Pro-environmental voters, those who during the last elections in Spain based their voting decision on whether the political party included pro-environment measures in its electoral program (n = 190), and 2) Non-Pro-environmental voters, those other people who voted for a political party without considering whether pro-environment measures were included in its electoral program (even if such environmental protection measures had been included) (n = 224). The results indicate that, in comparison with their counterparts who do not vote for pro-environmental parties, those who voted for political parties during the last elections by considering the inclusion of pro-environment measures in their electoral program showed the highest scores on the biospheric and socio-altruistic values of ecocentrism, anthropocentrism, connectivity with nature and environmental concern, and scored lower on self-centered values. With the exception of connectivity with nature, biospheric values and beliefs were good predictors of pro-environmental voting behavior.